CAN RESERVATIONS IN INDIA BE REMOVED AS IN BANGLADESH? - DEVARAPALLI, GOWTHAM (IJRDO - Journal of Social Science and Humanities Research, 2018)
Discrimination exists in each and every part of the world in one form or the other, on the basis of caste, color, race, religion and sex. The caste discrimination prevails in the countries of Indian sub-continent like India, Nepal, Sri Lanka, Pakistan and Bangladesh. Reservation provisions were made to address this historical blunder in the Indian Constitution. This is a 70 years compensation for 3000 years atrocity. From Gandhi to Goswami, the Upper Caste Urban Elite in India are always critical about this system of representation. With Bangladesh recently abolishing its 45 year old Quota system, the Indian question of abolition came once again into limelight. This paper examines the evolution of reservation system, its role in bringing the marginalized into the mainstream and the possibility of abolishing it.